Functional characterization in Caenorhabditis elegans of transmembrane worm-human orthologs - Henricson, Anna (BioMed Central, 2004)
BACKGROUND: The complete genome sequences for human and the nematode Caenorhabditis elegans offer an opportunity to learn more about human gene function through functional characterization of orthologs in the worm. Based on a previous genome-wide analysis of worm-human orthologous transmembrane proteins, we selected seventeen genes to explore experimentally in C. elegans. These genes were selected on the basis that they all have high confidence candidate human orthologs and that their function is unknown. We first analyzed their phylogeny, membrane topology and domain organization. Then gene functions were studied experimentally in the worm by using RNA interference and transcriptional gfp reporter gene fusions. RESULTS: The experiments gave functional insights for twelve of the genes studied. For example, C36B1.12, the worm ortholog of three presenilin-like genes, was almost exclusively expressed in head neurons, suggesting an ancient conserved role important to neuronal function. We propose a new transmembrane topology for the presenilin-like protein family. sft-4, the worm ortholog of surfeit locus gene Surf-4, proved to be an essential gene required for development during the larval stages of the worm. R155.1, whose human ortholog is entirely uncharacterized, was implicated in body size control and other developmental processes. CONCLUSIONS: By combining bioinformatics and C. elegans experiments on orthologs, we provide functional insights on twelve previously uncharacterized human genes.